Transfusion pattern of blood products in a blood bank at a tertiary care hospital - Dr. Jeevaraj Giridharan; Dr. V. Sarada (Tropical Journal of Pathology and Microbiology, 2020)
Objectives: Blood products in modern-day transfusion practice include, Packed Red Blood Cells, Platelets, Leucocytes, Plasma, Cryoprecipitate, and individual plasma factors. The objective was to study the pattern of usage of various blood products for the commonest clinical indications and to have an overview of the production of blood components. Materials and Methods: In this study, usage of various blood products like Packed Red Blood Cells, Platelet concentrates, Fresh Frozen Plasma, and Cryoprecipitate were studied in the blood bank of Trichy SRM medical college hospital and research center, using blood bank records and correlating with clinical data during the period of June 2015 - June 2020. Observation and result: The pattern of usage among 14,511 units of blood components from June 2015 – June 2020 showed the frequency of usage of Packed Red Blood Cells was more than Fresh Frozen Plasma and whole blood. The usage of whole blood was more than Platelet concentrates and Cryoprecipitate. The most frequently used component was Packed Red blood cells – 7841 units (54%). The second most frequently used component was fresh frozen plasma – 3889 units (26.8%). In the next frequency whole blood- 1955 units (13.5%), platelet concentrates - 797 units (5.5%) and cryoprecipitate – 29 units (0.2%) were used. Conclusion: There has been an appropriate increase in the usage of blood products to meet the clinical demand in treating the patients with an increase in pathological conditions. Specific blood component transfusion should be encouraged for specific indications to reduce non-essential overload to the patients.